Zoom fatigue and burnout among traditional, hybrid, and distance counselor educators - Fergel, Heidi (Kansas State University, 2024)
Utilization of online programs in higher education continues to rise. Although online counselor education programs are also rising, few studies explore the personal and professional consequences of these modalities on counselor educators. Therefore, this study examined differences in burnout and Zoom fatigue scores among traditional, hybrid, and distance counselor educators. The results of this study show that there were no significant differences in burnout or Zoom fatigue among these three groups. These findings suggest that counselor educators may be getting more familiar with online teaching and experiencing fewer negative personal and professional consequences.
Keywords: Zoom; Counselor; Educators; Burnout; Online; Distance